Situation of Iron Deficiency and Its Management Prioritizing Dietary Intervention in Nepal - Adhikari, B K; Koirala, U; Lama, STA; Dahal, P (Nepal Journal of Epidemiology, 2012)
Background Control of iron deficiency disorders is prioritized in the nutrition policies of Nepal. The situation is still threatening the public health in both rural and urban areas. Objective There are limited reviews on the iron deficiency situation in Nepal. This study was undertaken to find out the extent of iron deficiency anemia and intake of dietary iron among the general population in Nepal. Materials and methods Published research articles, books, bulletins, and online materials regarding iron deficiency were studied in both national and international scenarios. Results Nearly 46 percent of children (6–59 months) and 35 percent of women (15–49 years) were still suffering from anemia though the trend has been decreasing for the last 15 years. Mostly, young children (6–23 months) and pregnant women were the victims due to their high iron requirements and lower intake of dietary iron. The most common risk factors related to iron deficiency anemia (IDA) found in different studies were low intake of dietary iron, vitamin A deficiency, hookworm infection, malaria, heavy menstrual blood loss, and multiparity. Iron deficiency situation in the Nepalese population is triggered by Illiteracy, lack of awareness, negligence, poor economy, food insecurity, lack of food diversity, changes in dietary behavior, cultural behaviors, poor health and sanitation, and patriarchal structure of the society. Conclusion The main risk factor of IDA is low intake of dietary iron. There is a need of multiple approaches to address IDA with more focus on dietary iron to reduce anemia. DOI: http://dx.doi.org/10.3126/nje.v2i2.6573 Nepal Journal of Epidemiology 2012;2(2):182-190